Transcatheter treatment of complex pulmonic and aortic valvular disease following failed Ross procedure. Issue 12 (13th December 2021) - Aziz, Mohammad; Sidhu, Rajbir; Stinis, Curtiss T.
Abstract: A 63‐year‐old man with congenital bicuspid aortic valve disease and complex surgical history (that includes a Ross procedure complicated by cardiac arrest requiring emergency coronary artery bypass graft surgery, multiple subsequent sternotomies to treat a failed pulmonic homograft and pseudoaneurysm repair of the left and right ventricular outflow tracts (LVOT/RVOT), bioprosthetic aortic valve replacement, and aortic valve endocarditis) presented with worsening heart failure symptoms secondary to bioprosthetic aortic valve failure and recurrent pulmonic valve stenosis successfully treated with transcatheter intervention. Abstract :